The effect of psychoeducation on parents of autistic children in Malaysia - Ling, Lee Jye; Teng, Crendy Tan Yen (International Journal of Public Health Science (IJPHS), 2025)
Parents have reported a lack of support from professionals in Malaysia, which results in a lack of knowledge in supporting their children, leading to negative attitudes towards their child’s condition, a lack of empowerment, and psychological problems. This study aimed to determine the effect of psychoeducation on the knowledge, attitude, empowerment, and psychological well-being of parents of children with autism spectrum disorder (ASD). The design of this study was true experimental design. The study focused on parents of ASD-diagnosed children aged 2 to 7 years. Nineteen parents participated and were randomly allocated to the intervention group and control group. Pre and post-tests questionnaires assessed knowledge, attitude, psychological well-being, and empowerment. Independent and paired t-tests were used for data analysis. The results showed that there were no significant differences between the control and intervention groups in their knowledge (t(17)=-.186, p=.854), attitude (t(14.9)=1.26, p=.227), psychological wellbeing (t(13.44)=.221, p=.828) and empowerment (t(15.45)=.047, p=.96). There were no significant differences in the pre and post-sessions of the knowledge (t(9)=1, p=.329), attitude (t(9) =.536, p=.605), and psychological well-being (t(9)=.67, p=.521). However, there was a significant difference in the pre and post-session parent’s empowerment (t(9)=-2.5, p=.032). These findings suggest that other interaction factors may affect the effectiveness of psychoeducation sessions in parent’s knowledge, psychological wellbeing, attitude, and empowerment.